Studi Eksperimental Karakteristik Output Tegangan pada Variasi Susunan Seri-Paralel Modul Thermoelectric Generator (TEG) - Rizki Ramadhani, Nazla (Universitas Negeri Surabaya, 2025)
The utilization of waste heat energy through Thermoelectric Generator (TEG) technology is a solution in energy conservation, but the optimization of its electrical output is highly dependent on understanding the electrical characteristics and module circuit configuration. The main issue in this study is how the number of modules and the type of circuit affect the voltage produced. This study aims to analyze the effect of the number of TEGs in series and parallel circuits. The method used was experimental with independent variables of the number of modules (2 and 3 units) and the type of circuit in the SP1848 27145 SA type module made of Bismuth Telluride, while maintaining a constant temperature using a hot water source and ice cubes. The results showed that in a series circuit, adding TEGs significantly increased the voltage from around 2.9 volts to 3.3 volts. Conversely, in parallel circuits, the addition of modules did not directly increase the voltage, which tended to remain constant in the range of 1.73 volts to 1.74 volts. The conclusion of this study confirms that series configuration is more effective for achieving voltage increases, while parallel circuits provide output stability that supports the development of efficient thermoelectric power generation systems. Keywords: Bismuth Telluride, Seebeck Effect, Voltage, Thermoelectric Generator.